2018
DOI: 10.1002/jclp.22639
|View full text |Cite
|
Sign up to set email alerts
|

A four‐year longitudinal study examining psychache and suicide ideation in elevated‐risk undergraduates: A test of Shneidman's model of suicidal behavior

Abstract: Results provided partial support for Shneidman's contention of the importance of psychache for suicidal behavior and that other psychological factors are only important to suicide insofar as they relate through psychache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
3
27
0
2
Order By: Relevance
“…Our results strengthen the hypothesis that psychological pain is a construct that predicts suicidal events independently of depressive symptomatology [3, 4]. On the contrary, Trakhtenbrot et al [5] did not find that psychological pain was predictive of future SA.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Our results strengthen the hypothesis that psychological pain is a construct that predicts suicidal events independently of depressive symptomatology [3, 4]. On the contrary, Trakhtenbrot et al [5] did not find that psychological pain was predictive of future SA.…”
supporting
confidence: 87%
“…Shneidman [2] defined it as “psychache,” an acute state of intense psychological pain associated with feelings of guilt, anguish, fear, panic, loneliness, and helplessness, which is at the core of the suicidal process. Previous research in 2 cohorts of students at high risk of suicide showed baseline psychological pain and variations in psychological pain to be stronger predictors of suicidal ideation (SI) than depression or hopelessness during follow-up [3, 4]. However, a prospective study in 153 psychiatric inpatients showed that baseline psychological pain did not predict a future suicide attempt (SA) [5].…”
mentioning
confidence: 99%
“…Unbearable psychache also accounted for unique information in suicidal desire over and above these other variables. In addition, recent research suggests unbearable psychache is a primary motivation for suicide (May & Klonsky, ; May et al., ) and that psychache is a more important predictor of suicidal ideation than depression or hopelessness (Montemarano, Troister, Lambert, & Holden, ). Thus, taken together with other work, our findings suggest that incorporating unbearable psychache in risk assessments may provide clinicians with essential information pertaining to suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…The last four items ask respondents to endorse how strongly they agree or disagree with the experience described in each item, ranging from 1-strongly disagree to 5strongly agree. Psychometric properties of the Psychache Scale have been established in previous research demonstrating excellent scale reliability and good validity (Holden et al, 2001;Mills, Green, & Reddon, 2005).…”
Section: Samplementioning
confidence: 99%
“…The mediating effect of psychache was demonstrated between perfectionism and suicidal ideations, 40 between general distress and suicidal ideations, 19 and between childhood traumas and suicidal ideations. 41 Montemarano et al 42 conducted a 4-year follow-up study that supported Shneidman's model and pointed out that other factors were increasing the risk for suicide only when they were associated with psychache. In the Turkish population, previous studies revealed that the average PS score of patients with major depressive disorder 25 We found the mean score of PS as 37.6 ± 15.3 in the OCD and 23.6 ± 7.1 in the control group.…”
Section: Discussionmentioning
confidence: 93%